Light-Curing Units: A Review of What We Need to Know. (September 2015) - Price, R.B.; Ferracane, J.L.; Shortall, A.C.
For improved interstudy reproducibility, reduced risk of premature failures, and ultimately better patient care, researchers and dentists need to know how to accurately characterize the electromagnetic radiation (light) they are delivering to the resins they are using. The output from a light-curing unit (LCU) is commonly characterized by its irradiance. If this value is measured at the light tip, it describes the radiant exitance from the surface of the light tip, and not the irradiance received by the specimen. The value quoted also reflects only an averaged value over the total measurement area and does not represent the irradiance that the resin specimen is receiving locally or at a different moment in time. Recent evidence has reported that the spectral emission and radiant exitance beam profiles from LCUs can be highly inhomogeneous. This can cause nonuniform temperature changes and uneven photopolymerization within the resin restoration. The spectral radiant power can be very different between different brands of LCUs, and the use of irradiance values derived from dental radiometers to describe the output from an LCU for research purposes is discouraged. Manufacturers should provide more information about the light output from the LCU and the absorption spectrum of their resin-based composite (RBC). Ideally, future assessments and research publications should include the following information about the curing light: 1) radiant power output throughout the exposure cycle and the spectral radiant power as a function of wavelength, 2) analysis of the light beam profile and spectral emission across the light beam, and 3) measurement and reporting of the light the RBC specimen received as well as the output measured at the light tip.